Gestion des déchets ménagers : comment les collectivités françaises mobilisent-elles leurs usagers ? - Fanny Tarrisse-Vicard; Johanna Le Conte; Olivier Aznar; Anne Antoni; Raphaële Ferzli; Julie Gouet (VertigO)
This research aims at studying the actions developed by local authorities in order to lead households to adopt pro-environmental behaviours. Our research combines two complementary approaches. On the one hand, based on an economic approach, we analyze which choices make local authorities in order to encourage users of waste disposing services to throw away less waste. Within this framework we have established a typology of levers developed by local authorities. Then, based on an econometric study, we have pointed out the importance for local governments of taking into account households’ characteristics in the definition of their waste management strategy.On the other hand, based on a human and social sciences approach, we notice a complex relationship between users and waste management service, as well as sorting practices tightly embedded in individuals’ everyday life.